Заохочення студентів до самовдосконалення: досвід України та Великої Британії (початок ХХІ століття) - Филипська, В. І.; Fylypska, V. I.; ORCID: http://orcid.org/0000-0003-0497-7196 (Наукові записки [Центральноукр. держ. пед. ун-ту імені Володимира Винниченка]. Сер.: Педагогічні науки. - 2021. - Вип. 194. - С. 177-183, 2021)
Виявлено на основі історико-педагогічного аналізу теоретичні ідеї та проаналізовано досвід заохочення студентів до самовдосконалення в Україні й у Великій Британії на початку XXI cт. для використання педагогічно цінних методів заохочення студентів у практиці роботи сучасних вищих навчальних закладів України. Розкрито проблему заохочення студентів вищих навчальних закладів до самовдосконалення. Розглянуто заохочення студентів до самовдосконалення як сукупність взаємопов`язаних і взаємодіючих структурних компонентів, направлених на стимулювання саморозвитку, розвитку механізмів рефлексії та самореалізації. Визначено функції самовдосконалення та заохочення.

The article reveals the problem of encouraging students of higher educational institutions to selfimprovement. In this study, encouraging students to self-improvement is considered as a set of interconnected and interacting structural components aimed at stimulating self-development, development of mechanisms of reflection and self-realization. The functions of self-improvement and encouragement are defined. The mechanism and stages of student encouragement are analyzed. The elements of self-improvement are characterized in detail in the work. Forms (external and internal) and methods of stimulating students to self-improvement are identified, based on the experience of Ukraine and Great Britain during the development of this problem in science – the beginning of the XXI century. Incentive methods are described in terms of their effectiveness. The paper focuses on modern conditions of effective self-improvement of students and it has been found that in order to be competitive and successful in the professional sphere, a modern student should gain a process of self-improvement and a modern teacher– to encourage him/her with different methods. Prospects for further research are identified, which should be aimed at scientifically domestic and foreign experience towards the analysis and selection of effective techniques, methods and means of encouraging students to self-improvement, which the teacher will be able to use in practice. Their value orientations, interests and motives, beliefs, ideas about goals or intentions, as well as professional competence play an important role in the process of forming students' readiness for successful professional activity. It is a complex structured picture that includes both the self and relationships with other people, as well as positive and negative beliefs. It is largely due to the preparation of the student in the university. Creating a strong positive inner image of thoughts about a particular field of activity, professional competence and continuous self-development will ensure success. Such a statement of the problem requires not only effective methods for the formation of a successful specialist, but also the creative organization of the pedagogical process, the creation of appropriate conditions for the formation of students' focus on successful professional activity.

Выявлены на основе историко-педагогического анализа теоретические идеи и проанализирован опыт поощрения студентов к самосовершенствованию в Украине и Великобритании в начале XXI в. для использования педагогически ценных методов поощрения студентов в практике работы современных вузов Украины. Раскрыта проблема поощрения студентов высших учебных заведений к самосовершенствованию. Рассмотрено поощрение студентов к самосовершенствованию как совокупность взаимосвязанных и взаимодействующих структурных компонентов, направленных на стимулирование саморазвития, развитие механизмов рефлексии и самореализации. Определены функции самосовершенствования и поощрения.
Филипська, В. І. Заохочення студентів до самовдосконалення: досвід України та Великої Британії (початок ХХІ століття) / Филипська Віта Іванівна // Наукові записки [Центральноукр. держ. пед. ун-ту імені Володимира Винниченка]. Сер.: Педагогічні науки. - 2021. - Вип. 194. - С. 177-183. - DOI: 10.36550/2415-7988-2021-1-194-177-183.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зарубіжний досвід; foreign experience; зарубежный опыт; Велика Британія; United Kingdom; Великобритания; заохочення студентів; encouraging students; поощрение студентов; заохочення до самовдосконалення; encouragement for self-improvement; поощрение к самосовершенствованию; самовиховання; self-education; самовоспитание; самоосвіта; самообразование; мотивація; motivation; мотивация